Mercy : Altee Pine #4 - Baldacci, David (New York : GCP, 2021)
"The #1 New York Times bestselling author with 150 million copies sold worldwide returns with his next blockbuster thriller featuring FBI Agent Atlee Pine"--.
Keywords: Suspense fiction; Mystery; Detective and mystery stories; Crime